TikTok and the translingual practices of Filipino domestic workers in Hong Kong. (December 2022) - Darvin, Ron
Abstract: Recognizing the immense popularity of TikTok among the over 200, 000 Filipino domestic workers in Hong Kong, this paper examines the translingual practices of these migrants from the Global South on a social media platform known for its act out memes, dance and lip-synch videos. Drawing on data from interviews and the multimodal discourse analysis of TikTok profiles, videos and captions, it pays particular attention to how recognizing these practices not as exotic or creative transgressions but as ordinary or normative (Agha, 2007) can enable a critical understanding of the lived experiences of these transnationals. Findings show that as they move across social media platforms and make linguistic and semiotic choices involving practical and material considerations, they perform moments of interaction or "small things" (Blommaert, 2019) online that are not unlike their mundane, offline counterparts. Moving across languages online is a way for users to negotiate multiple identities, position others, address diverse audiences, and signal group affiliations. By examining translingual interactions on social media as normative but negotiated across different orders of indexicality, this paper asserts that such reframing can draw attention to historical and material inequalities and modes of exclusion online.